2013
DOI: 10.1007/s12032-013-0532-9
|View full text |Cite
|
Sign up to set email alerts
|

Significant frequency of allelic imbalance in 3p region covering RARβ and MLH1 loci seems to be essential in molecular non-small cell lung cancer diagnosis

Abstract: The aim of the study was to investigate the influence of allelic imbalance (AI) in several loci of tumor suppressor genes in 3p region on the non-small cell lung cancer (NSCLC) development. We evaluated the frequency of loss of heterozygosity and/or microsatellite imbalance (LOH/MSI) and assessed their association with patients’ characteristics (age, gender, tobacco addiction) and NSCLC classification according to TNM/AJCC staging. To analyze the potential role of AI involved in NSCLC pathogenesis, we alleloty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…However, studies indicate that hMLH1 expression is under regulation by different methods. Homozygous deletions, allelic deletion, and point mutations have also been found to attenuate hMLH1 expression 4446. Specifically, hMLH1 protein acting as a part of DNA repair pathways undergoes hypoxia regulation via epigenetic modulation as well as transcriptional and translational regulation 45…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies indicate that hMLH1 expression is under regulation by different methods. Homozygous deletions, allelic deletion, and point mutations have also been found to attenuate hMLH1 expression 4446. Specifically, hMLH1 protein acting as a part of DNA repair pathways undergoes hypoxia regulation via epigenetic modulation as well as transcriptional and translational regulation 45…”
Section: Discussionmentioning
confidence: 99%
“…Antczak et al44 reported that reduced hMLH1 expression due to allelic imbalance combined with epigenetic alteration was more frequently associated with heavy smokers; however, a correlation could not be determined between hMLH1 methylation and the smoking characteristic (smoking history) of the individuals with NSCLC due to lack of quantitative data.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, FHIT has been documented to be in correlation with lifetime cigarette addiction (Antczak et al, 2013). This existing result, combined with our finding that FHIT is associated with alcohol dependence, partially supports the hypothesis that common genes underlie the comorbidity of multiple substance dependencies.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple impaired expression of the RARs and RXRs can occur through genetic events such as epigeneticchanges, homozygous deletion, intragenic mutation, rearrangement of chromosomal material and loss of heterozygosity (LOH) followed by a second hit, which plays a major role in cancer initiation and progression [35].…”
Section: Genetic Alterations Of Rar and Rxr Expression In Lung Cancermentioning
confidence: 99%
“…The LOH has been identified as the initial event in lung carcinogenesis, and it is recognized in multiple chromosomal regions [35] [47] [48]. Frequently the 3p21 region contains a distinct locus that is sensitive to loss from the action of tobacco smoke carcinogens and has been reported as a biomarker in the genetic classification of pathological stages of NSCLC [48]- [50].…”
Section: Genetic Alterations Of Rar and Rxr Expression In Lung Cancermentioning
confidence: 99%